RESEARCH ON PERFORMANCE OPTIMIZATION METHOD OF MECHANICAL PARTS BASED ON CAD/CAE INTEGRATION - WU Qiang; LIU FuYun; HU RuKai; YU HanHong (Jixie qiangdu)
Aiming at the problems of low efficiency, long cycle and difficulty in quality assurance in product design faced by most manufacturing enterprises, performing research on parameterized CAD and CAE technology, as well as the data transmission between software CAD and CAE, a general design method for optimizing the performance parameters of mechanical parts based on CAD/CAE integration was proposed. This method took Visual Studio as the platform, used APDL and C++ language for redeveloped ANSYS and Solid Works respectively, and developed a digital design system of mechanical parts based on CAD/CAE integration. After changing the parameter value, the system solves the finite element solution automatically and quickly, the solution results are automatically output to the specified path, and the solution results are automatically opened and locked. Taking the design of inner ring of driven plate for example, the three-dimensional（3 D） model and solution results were quickly obtained by this method. The research results show that this method is feasible and universal.